Challenges To The Security Address; Resilience – A Way Of Response - Repez, Filofteia; Olar, Polixenia (Acta Universitatis Danubius. Relationes Internationales, 2023)
The challenges to security, some unpredictable, others predictable, determine the elaboration and development of understanding, prevention and reaction mechanisms both on the part of states, when national security is affected, and on the part of international and regional organizations, when international security and regional is affected. Whether they belong to valued public or private voices, knowing and understanding the evolution and consequences of these issues are beneficial to academia. Along with these mechanisms, resilience has increasingly become a way of responding to security challenges. In this sense, the present article presents the main problems of the 21st century from two approaches - a private approach and a public approach, continuing with the presentation of some aspects of resilience as a way to deal with moments of insecurity.